SOME EXACT SOLUTIONS OF (3+1)-DIMENSIONAL SHALLOW WATER WAVE EQUATION AND (2+1)-DIMENSIONAL FIFTH-ORDER NONLINEAR EQUATION - Ic, Unal (Editura Bibliotheca-Bibliotheca Publ House, 2019)
In this paper, we implemented an improved tanh function Method for some exact solutions of (3+1)-dimensional Shallow water wave equation and (2+1)-dimensional fifth-order nonlinear equation.
Keywords: (2+1)-dimensional fifth-order nonlinear equation; (3+1)-dimensional shallow water wave equation; exact solutions; improved tanh function method